2021
DOI: 10.1016/s2589-7500(21)00039-x
|View full text |Cite|
|
Sign up to set email alerts
|

Prognostication of patients with COVID-19 using artificial intelligence based on chest x-rays and clinical data: a retrospective study

Abstract: Background Chest x-ray is a relatively accessible, inexpensive, fast imaging modality that might be valuable in the prognostication of patients with COVID-19. We aimed to develop and evaluate an artificial intelligence system using chest x-rays and clinical data to predict disease severity and progression in patients with COVID-19. Methods We did a retrospective study in multiple hospitals in the University of Pennsylvania Health System in Philadelphia, PA, USA, and Bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
103
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(118 citation statements)
references
References 25 publications
2
103
1
Order By: Relevance
“…Whereas many studies have investigated AI applications for diagnosis and prognosis during the pandemic [23][24][25][26] , key reviews highlight sector-wide methodological and reporting concerns that threaten generalisability, questioning the suitability of many models to-date for clinical use [27][28][29] . Reviewing the contribution of AI to the COVID-19 response, a recent editorial highlighted the promise of CURIAL-1.0 amongst other solutions to support patients during the pandemic, discussing the importance of highquality validation studies inclusive of diverse patient populations 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Whereas many studies have investigated AI applications for diagnosis and prognosis during the pandemic [23][24][25][26] , key reviews highlight sector-wide methodological and reporting concerns that threaten generalisability, questioning the suitability of many models to-date for clinical use [27][28][29] . Reviewing the contribution of AI to the COVID-19 response, a recent editorial highlighted the promise of CURIAL-1.0 amongst other solutions to support patients during the pandemic, discussing the importance of highquality validation studies inclusive of diverse patient populations 30 .…”
Section: Introductionmentioning
confidence: 99%
“…It also achieved similar accuracy and sensitivity with the B1 and B3-X (6.6 and 12.3 million parameters respectively). Jiao et al [ 38 ] also used EfficientNet as the baseline ConvNet, but the prediction was different (COVID-19 severity: critical vs. non-critical), and the model was considerably more complex: it connected a convolutional layer (256 neurons) and a dense layer (32 neurons) on top of the baseline. Despite its complexity, the model did not perform as well on an external dataset: accuracy of 75% (95% CI 74, 77), sensitivity of 66% (95% CI 64, 68), and specificity of 70% (95% CI 69, 71).…”
Section: Discussionmentioning
confidence: 99%
“…The main limitation of our study is the lack of patient data. We appreciate that the model built by Jiao et al [ 38 ] included patient clinical data (e.g., age, sex, oxygen saturation, biomarkers, comorbidities), which slightly improved the accuracy of the image-based CNN. We recognize that this is an important avenue for future research.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers had collected the X-ray samples from 1834 patients and used the artificial chest X-rays to predict the progression and severity of the COVID-19 disease. It was found that the AI based chest X-rays had better diagnosis in comparison to radiologist derived severity scores and clinical data [ 18 ]. Furthermore, convolutional neural network (CNN) was used by researchers to analyse chest X-rays in order to identify COVID-19 and its conditions.…”
Section: Ai Application For Imaging and Diagnosis Of Covid-19mentioning
confidence: 99%